Effectiveness of automated writing evaluation program to enhance EFL undergraduates’ writing performance in China - Geng, Jingxin; Razali, Abu Bakar; Ismail, Lilliati; Noordin, Nooreen (Springer Science and Business Media B.V., 2024)
Automated writing evaluation (AWE) program has huge potential to facilitate English writing instruction and EFL learners’ learning. As one of the most massively implemented AWE programs in China, the Pigai program has gained increasing ground in English writing instruction. However, a paucity of research limits to addressing its effects as an assisted teaching tool. Therefore, this study was conducted to ascertain the effect of the AWE-Pigai assisted process-based approach in improving Chinese EFL undergraduates’ writing performance and their error correction ability. As such, three intact classes from the first year in English major at a university in China were recruited. They received three different teaching approaches respectively: the Process-based writing approach (PBWA), the combined use of the Pigai program and the PBWA (Pigai + PBWA), and the conventional teaching approach. After a 14-week training program and a month after the intervention, students’ writing performance at three different time slots were compared, i.e., pre-, post-, and post-delayed tests. Results indicated that the Pigai + PBWA was able to outperform the other two methods in improving students’ writing performance and displayed a better post-delay effect in internalizing students’ writing knowledge in their long-term memory. Finally, the pedagogical implications of this study were also discussed. © 2024, Education Research Institute, Seoul National University.